Optical spectrum CDMA: A new code construction with zero cross correlation for double weight code family - Babekir, E.I.; Saad, N.M.; Elfadel, N.; Mohammed, A.; Aziz, A.A.; Anuar, Mat Safar; Syed Alwee Aljunid, Syed Junid; Mohamad Khazani, Abdullah (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org